COUP-TFII Gene Expression is Upregulated in Embryonic Pleuroperitoneal Folds in the Nitrofen-Induced Congenital Diaphragmatic Hernia Rat Model - Dingemann, J.; Doi, T.; Ruttenstock, E.M.; Gosemann, J.H.; Puri, P. (European Journal of Pediatric Surgery, 2012)
Introduction The nitrofen model of congenital diaphragmatic hernia (CDH) creates a Bochdalek-type diaphragmatic defect and has been widely used to investigate the pathogenesis of CDH. However, the exact pathogenesis of the diaphragmatic defect in this model is still poorly understood. Chicken ovalbumin upstream promotor-transcription factor II (COUP-TFII) is expressed in the embryonic pleuroperitoneal folds (PPF) in the early stage of development and in the diaphragm in the late days of gestation. COUP-TFII is known to be a strong repressor of the retinoid signaling pathway (RSP), which plays an important role in diaphragm development. Furthermore, it has been recently shown that COUP-TFII is upregulated during early gestation in the nitrofen-induced hypoplastic lung. We designed this study to investigate the hypothesis that COUP-TFII gene expression is upregulated during early diaphragmatic development in the PPF.Material and Methods Timed pregnant rats were exposed to either olive oil (Control) or nitrofen (CDH) on day 9 of gestation (D9). Fetuses were sacrificed on D13, D18 or D21. The PPF was dissected from D13 fetuses using laser capture microdissection. Diaphragms were dissected from D18 and D21 fetuses under the dissection microscope. The relative mRNA expression levels of COUP-TFII were determined using real-time PCR. Immunohistochemistry was performed to evaluate diaphragmatic protein expression and the distribution of COUP-TFII.Results On D13, gene expression levels of COUP-TFII in the PPF were significantly increased in the CDH group (82.93 ± 11.85) compared to Controls (46.22 ± 8.09; p < 0.05), whereas there were no differences at later time points. The immunoreactivity of diaphragmatic COUP-TFII was markedly increased in the PPF in the CDH group compared to Controls on D13. No difference in immunoreactivity was observed on D18 and D21.Conclusion Upregulation of COUP-II gene expression in the PPF may contribute to the diaphragmatic defect in the nitrofen CDH model by inhibiting the RSP.
Keywords: congenital diaphragmatic hernia; nitrofen model; diaphragmatic defect; COUP-TFII; retinoid signaling pathway